Essays in macroeconomics and applied econometrics using PPI microdata - Abib, Daniel Barboza Dale (2022)
This thesis investigates the firms’ price-setting behavior in Brazil for the 2008- 2020 period, focus on the dynamics of the price setting statistics over the business cycle, the exchange rate pass-through at firm level and the impact of the monetary policy and exchange rate shocks in the disaggregated price dynamics. This thesis is composed by three papers and in all of them we use a novel confidential microeconomic data collected by FGV IBRE to construct the Producer Price Index (PPI), the oldest producer price index in Brazil, released since 1947. This unique data set covers a wide variety of manufactured products, and the electronic micro data set is available since 2008. Another important feature of the data set is that it keeps the exact same item along a quote line as long as it exists, and never uses a similar item’s price in place of the original item. Those features are key for achieving quote lines that have an average length of 85.9 months for the same item, after our data treatments. We construct time series of price-setting statistics, such as frequency of price changes, size of price changes and sample inflation. In all papers we use these statistics.